ANALISIS PRODUKTIVITAS USAHA PETERNAKAN AYAM BROILER SISTEM KEMITRAAN DI KECAMATAN PLOSOKLATEN KABUPATEN KEDIRI - Ertika Fitri Lisnanti; Indra Setiawan (Jurnal Ilmiah Fillia Cendekia, 2016)
The level of knowledge, attitudes and skill of broiller farmers in Kecamatan Plosoklaten Kabupaten Kediri already in a good condition, but there were still some farmers that are not care about procedures of good farming practices and profitable farming practices. The methods that used in this research was a surveying method, withgathering a great quantity of variables through a interview in the form of a list of questions shaped a the questionnaire. Population in this research wasall farms with the same business partnership, from 30 farmers with 3 different business partnerships. The sample of this research was 14 farmers in a same business partnership in Kecamatan Plosoklaten and then grouping in to 3 based on stratification. The result showed 8 small scale farmers and 3 big scale farmers. The average of farmers income in a period wasRp 6.146.279 in small scale farms, Rp 7.066.910 and Rp 8.885.064 in big scale farms. BEP in small scale farms 4.508/Kg, in medium scale farms 7.692/Kg and in a big scale farms 10.237/Kg. R/C ratio in small scale farms 1,02, in medium scale farms 1,07 and in a big scale farms 1,11. Broiller farming in Kecamatan Plosoklaten Kabupaten Kediri worthed to continue because the average of R/C ratio was >1.